Website learning media to enhance planning tour packages competencies: A case study from Makassar Tourism Polytechnic, Indonesia - Windra Aini; Darmayasa Darmayasa; Ruth Rinda; Ahmad Tarmizi Abdul Karim; Agus Sugiarto; Andri Estining Sejati; Masri Ridwan (Universitas Negeri Malang, 2024)
This research aims to develop website-based learning media on tourism package planning competency and report its feasibility. In particular, this study aims to address the challenges posed by the COVID-19 pandemic, which has made it difficult to conduct field trips or study tours, a crucial component of the travel business study program at Politeknik Pariwisata Makassar. The research addopted a research and development (R&D) approach with the ADDIE model, as well as involving the material experts and media experts in the media assessments. Learning media trials were conducted in small groups comprising ten students and in large groups with 30 students. The learning media development resulted in a website hosted on the Google Site at https://sites.google.com/view/membuat-paket-wisata/halaman-muka. The expert assessment of the media's learning content and teaching process obtained an average score of 4.56 in the very good category. Meanwhile, the assessment of media experts on appearance and programming obtained an average score of 4.41 in the very good category. Similarly, the product trials involving students also culminate in an average score of 4.45 in the excellent category. In general, the results of the assessment and trials concluded that website-based learning media is feasible to be adopted in the competence of planning tour packages.